AVALIAÇÃO DO ESTRESSE E DEPRESSÃO E SUA ASSOCIAÇÃO COM BIOMARCADORES EM CUIDADORES DE IDOSOS COM DOENÇAS NEURODEGENERATIVAS - Bakof, Karstyn Kist (2019)
The older population is increasing in the world and concomitant with there are an enhance in the neurodegenerative disease, characterized by a progressive decline in the areas of cognition and behavior. While the disease progresses, there is the demand for a special care, an important activity performed by caregivers. Caring someone impacts on the quality of life of the caregivers and the burden experienced daily can cause emotional changes and physical overload, reflecting somatic diseases, social isolation, higher prevalence of psychiatric illness, such as depression and stress, characteristics of the Burnout Syndrome. Psychological stress has been associated with an increased risk of developing depression and studies suggest that caffeine may act as a protective factor for this disorder. The present work is arranged in two chapters and aims to evaluated the influence of stress and depression on the physical and mental health of caregivers of the elderly with neurodegenerative disease. Chapter 1 presents the field study, where 81 caregivers (family members or professional) of the elderly with neurodegenerative diseases from community, recruited from July 2018 to April 2019. Caregivers were evaluated for stress and depressive symptoms using psychological questionnaires (Hamilton Depressive Rating Scale and Lipp’s Inventory of Stress Symptoms for adults). Also, they answered a 72-hours Recall to evaluate caffeine intake and collected saliva for the measurement of salivary biomarkers. The field study showed that stress and depression symptoms are present in more than half of the population and that stress was associated with educational level, tobacco use and frequency of DNA damage. However, stress and depression indexes did not show association with caffeine consumption and other salivary biomarkers. Chapter 2 presents the narrative review from the scientific literature with the search in the PubMed, LILACS, SciELO, Web of Science and Scopus databases for publications between 2008 and 2018, with the following descriptors: [“Burnout prevalence” or “Burnout Syndrome” or “Burnout“ and (“caregivers” and “dementia”) or (“dementia elderly”)]. For review, 10 studies were included in the English language, because they present the prevalence of Burnout Syndrome using questionnaires appropriate for the evaluation of this syndrome. The majority shows a high prevalence of Burnout syndrome in caregivers of the elderly with dementia. The present dissertation corroborates the hypothesis that caregivers of the elderly with neurodegenerative diseases are exposed daily to stressful situations, increments knowledge about the impact of educational level as a preventive of psychological symptoms. Nevertheless, it indicates that investigated salivary biomarkers do not have a pattern of association of psychological stress with the burden of care in these caregivers.